CASE SERIES OF 7 ADRENOCORTICAL ONCOCYTIC NEOPLASMS, A SINGLE CENTRE EXPERIENCE - Ho, JH; Norazwa, R; Rafie, MK Mohamad; Masni, M (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Adrenocortical oncocytic neoplasm is an extremely rare disease, it is usually detected incidentally, and majority are benign and non-functioning. METHODOLOGY The demographic and clinical data of 7 patients with adrenocortical oncocytic neoplasm diagnosed and surgically treated at the department of endocrinology in Putrajaya Hospital, between January 2010 and March 2021, were retrospectively analyzed. The clinical manifestations, imaging examination, endocrine examination, types of surgery, pathological results and patient outcomes were analyzed. RESULTS The mean age at diagnosis was 41(18-68) years old, with female predominance (4:3), and left side dominance (6:1). In one patient, the tumour was incidentally found during staging for breast cancer. Three patients presented with flank pain. Three patients were diagnosed during evaluation for Cushing’s syndrome. The cortisol and catecholamine metabolites were normal except for 3 patients with Cushing’s syndrome. Four patients underwent laparoscopic resection of the tumour while the other 3 had open surgery. All surgeries were successfully performed with no complications. The median tumour size is 70 mm (30-180 mm) and the median weight of the tumour is 155.2 g (12.5-1914.3 g). The tumours exhibited the following immunohistochemical profiles: positive for vimentin n=6 (100%), synaptophysin n=5 (100%), neuronspecific enolase n=5 (100%), S-100 n=5 (60%); negative for cytokeratin n=6(83%) and chromogranin n=6 (66%). All the patients were regularly followed up. The follow-up period ranged from 3 to 136 months. The 3 patients with Cushing’s syndrome had clinical and biochemical resolution during follow-up. However, 1 case had recurrent Cushing’s syndrome with local and distant metastases. CONCLUSION The adrenocortical oncocytic neoplasms are rare and mostly benign tumours. Surgical resection is the main treatment method. Careful pathological examination and close follow-up are needed to confirm the prognosis.